Diurnal movement of plankton in a peninsular man-made lake - Singh, D N; Das, A K (Indian Journal of Fisheries, 2011)
Diurnal movement of plankton was studied in Manchanbele, a small man-made impoundment, during pre-monsoon, monsoon and post-monsoon seasons. Zooplankton showed a clear trend in diurnal movements than phytoplankton. Studies showed the dominance of plankton at 18 h (35.08%) than any other time of the day followed by 31.69% at 6 h. Minimum concentration was observed at 12 h. Maximum variation of 260 no./l was observed between 12 h and 18 h and minimum of 176 no./l between 6 h and 24 h. It was concluded that light may be one of the dominant factor affecting diurnal movements of plankton in the reservoir.